Assessing the financial performance of container shipping companies - Cai, Kewei (2009)
Over the past few decades, a phenomenon was observed where container shipping lines are adapting vertical integration strategies towards the ports and logistics market, which is outside of their core business. Despite the expected financial benefits that the vertical integration will bring, there is a lack of literature on this area to support the statement. The objective of this paper serves to analyze the impact of vertical integration on the financial performance of container shipping lines and fills in the missing literature gap in this area. Financial data was obtained from company annual reports and other available resources. The financial ratio comparison analysis performed to compare periods prior to and after vertical integration implied a weak correlation between financial performance and vertical integration. Findings seem to suggest that the improvement in financial performance was not fully attributed to the integration strategy but as well as to the economic conditions prevailing at that time.